Control in bioprocessing : modeling, estimation and the use of soft sensors /: modeling, estimation and the use of soft sensors. (2020) - López Pérez, Pablo Antonio, 1981-; Lopez, Ricardo Aguilar, 1964-; Femat Flores, Alejandro Ricardo
No abstract available